ADSORPTION OF DODECYLBENZENESULFONIC ACID ON THE ALUMINA PARTICLES IN THE PREPARATION OF ALUMINA FOAM - Zora Hajduchova; Ladislav Pach; Lokaj Jan (Ceramics-Silikáty, 2018)

(untitled)
Partially hydrophobized particles of α-Al₂O₃ were used to prepare the alumina foams. Dodecylbenzenesulfonic acid (DBSA) was applied to the hydrophobized surface of alumina particles. The infrared spectroscopy provided the evidence of the interaction (adsorption) of DBSA on the alumina surface. The quantity of DBSA adsorbed on the alumina particles was determined using Lambert-Beer law by measuring UV-VIS spectra. The mechanisms of DBSA adsorption on the surface of alumina particles may be attributed to (1) electrostatic interactions or (2) specific chemical reactions between the surfactant and the surface hydroxyl groups. Adsorption of DBSA on the alumina particles is strongly influenced by the pH of suspensions. The quantity of DBSA is not sufficient to hydrophobize alumina particles at pH up to about pH 9.5, as the electrostatic repulsion forces between the sulfonic group of DBSA and the alumina surface prevailed and the DBSA acts only as a surfactant. The foams were sintered at 1400 °C, 1450 °C, 1500 °C, 1550 °C and 1600 °C. The optimal sintering temperature was found to be 1550 °C. The maximal compressive strength of the alumina foams was ∼ 300 kPa while its porosity was relatively high (96.7 %).